A study on the pattern of non-communicable diseases and their effects on pregnancy outcomes in Kashmiri women - Kour, Abjeet; Aziz, Irtika; Jameel, Mohd; Chowdhary, Maria Mushtaq (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Non-communicable diseases (NCDs), such as chronic hypertension, diabetes, thyroid disorders and cardiovascular diseases, pose significant risks during pregnancy, contributing to adverse maternal and fetal outcomes. This study aims to examine the pattern of NCDs among pregnant women in Kashmir and evaluate their effects on pregnancy outcomes. Methods: A prospective observational study was conducted over 12 months at Lalla Ded Hospital, Srinagar, involving 450 pregnant women diagnosed with NCDs either before or during pregnancy. Data were collected on maternal demographics, type of NCD and pregnancy outcomes. Maternal and fetal complications were assessed, including APGAR scores, NICU admissions, delivery modes and maternal morbidity and mortality. Results: The most prevalent NCD was chronic hypertension (33.7%), followed by thyroid disorders (19.1%) and diabetes mellitus (15.1%). Of the 450 women, 250 (55.5%) had no complications, 176 (39.1%) had non-life-threatening complications, 20 (4.4%) experienced maternal near-miss events and 4 (0.8%) succumbed to their conditions. Regarding fetal outcomes, 84.8% were live births, 10.2% abortions, 3.1% intrauterine deaths and 1.7% stillbirths. APGAR scores were ≥8 in 73.2% of babies, while 31.2% required NICU admission. Conclusions: NCDs during pregnancy are prevalent and significantly impact both maternal and fetal health. Chronic hypertension was the most common condition, associated with increased rates of complications, caesarean delivery and NICU admissions. Early diagnosis, multidisciplinary management and improved antenatal care are crucial for optimizing fetomaternal outcomes in pregnancies complicated by NCDs.